Cellular and population plasticity of helper CD4+ T cell responses - Magombedze, Gesham; Reddy, Pradeep B.; Eda, Shigetoshi; Ganusov, Vitaly V. (Frontiers in Physiology, 2013)
Vertebrates are constantly exposed to pathogens, and the adaptive immunity has most likely evolved to control and clear such infectious agents. CD4 T cells are the major players in the adaptive immune response to pathogens. Following recognition of pathogen-derived antigens naïve CD4 T cells differentiate into effectors which then control pathogen replication either directly by killing pathogen-infected cells or by assisting with generation of cytotoxic T lymphocytes or pathogen-specific antibodies. Pathogen-specific effector CD4 T cells are highly heterogeneous in terms of cytokines they produce. Three major subtypes of effector CD4 T cells have been identified: T-helper 1 (Th1) cells producing IFN-g and TNF-α, Th2 cells producing IL-4 and IL-10, and Th17 cells producing IL-17. How this heterogeneity is maintained and what regulates changes in effector T cell composition during chronic infections remains poorly understood. In this review we discuss recent advances in our understanding of CD4 T cell differentiation in response to microbial infections. We propose that a change in the phenotype of pathogen-specific effector CD4 T cells during chronic infections, for example, from Th1 to Th2 response as observed in Mycobacteriumavium ssp. paratuberculosis (MAP) infection of ruminants, can be achieved by conversion of T cells from one effector subset to another (cellular plasticity) or due to differences in kinetics (differentiation, proliferation, death) of different effector T cell subsets (population plasticity). We also shortly review mathematical models aimed at describing CD4 T cell differentiation and outline areas for future experimental and theoretical research.